2022
DOI: 10.5001/omj.2021.69
|View full text |Cite
|
Sign up to set email alerts
|

Diet Adherence among Adults with Type 2 Diabetes Mellitus: A Concept Analysis

Abstract: Aim: To analyze the concept of diet adherence in type 2 diabetes mellitus (T2DM). Background: Different healthcare providers widely use the concept of adherence. In the 1970s, the term compliance was commonly used as the patients' views on treatment decisions were neglected. With consideration of patients' perspectives in treatment choices and treatment management, the concept of "compliance" has been increasingly replaced by "adherence." Adhering to a healthy diet is very challenging among patients with T2DM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
(44 reference statements)
2
10
0
4
Order By: Relevance
“…El tratamiento medicamentoso y las acciones no farmacológicas como la dieta adecuada y los ejercicios físicos son (28) imprescindibles para el adecuado control de la diabetes . La Organización Mundial de la Salud define la adhesión como "el grado en que el paciente sigue las instrucciones del profesional de la salud, a medida que hay cambio de comportamiento, entendida como tomar la medicación, seguir la dieta y / o (12,16,20) cambiar el estilo de vida"…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El tratamiento medicamentoso y las acciones no farmacológicas como la dieta adecuada y los ejercicios físicos son (28) imprescindibles para el adecuado control de la diabetes . La Organización Mundial de la Salud define la adhesión como "el grado en que el paciente sigue las instrucciones del profesional de la salud, a medida que hay cambio de comportamiento, entendida como tomar la medicación, seguir la dieta y / o (12,16,20) cambiar el estilo de vida"…”
Section: Discussionunclassified
“…Existen diversos cuestionarios diseñados para evaluar los constructos que componen el tratamiento del diabético, sobre todo la alimentación sana, actividad física regular, medicación constante y autoanálisis de glucemia capilar. La mala adherencia a la dieta es comúnmente debida a la falta de comprensión, implementación y mantenimiento de motivación, (12) comprensión, creencias sobre la salud, autoeficacia y el apoyo social . Pero estos factores pueden variar en el tiempo y en cada región.…”
Section: Introductionunclassified
“…Previous studies have also found that individuals with type 2 diabetes had poor adherence to exercise and a healthy diet (10,11). It would be difficult to sustain lifestyle changes (12), and efforts toward lifestyle modifications have the potential to cause emotional distress.…”
Section: Introductionmentioning
confidence: 97%
“…As a result, an algorithm is required to make it easier for the system to recognize, compare, and study foods automatically using image data, so that differences between the foods to be consumed can be discovered [ 13 ]. At this time, it is undeniable that information technology is rapidly evolving and tends to aid humans in completing tasks more quickly and efficiently [ 14 ]. It is very possible to create a computation that can process information from an image or image for automatic object recognition in this all-digital era [ 15 ].…”
Section: Introductionmentioning
confidence: 99%